Synthesis and efficacy of norfloxacin loaded onto magnetic hydrogel nanocomposites. Issue 48 (17th September 2021) - Salahuddin, Nehal; Rehab, Ahmed; Emad, Sahar
Abstract : A targeted drug delivery system based on biocompatible magnetic hydrogel nanocomposites consisting of poly[oligo(oxyethylene methacrylate)] anchored Fe3 O4 nanoparticles was synthesized. Abstract : A targeted drug delivery system based on biocompatible magnetic hydrogel nanocomposites consisting of poly[oligo(oxyethylene methacrylate)] anchored Fe3 O4 nanoparticles was synthesized. The characteristics, thermal properties, morphology and magnetic properties were studied by XRD, FT-IR, TGA, SEM, TEM and VSM. A norfloxacin (NOR) anti-bacterial agent with a potential antitumor activity was immobilized into hydrogels, Fe3 O4 nanoparticles and their magnetic hydrogel nanocomposites. The in vitro drug release manner of NOR was explored at different temperatures and pH values. The behavior of the drug release has been studied via different kinetic models. The antibacterial efficacy was tested against Streptococcus, Staphylococcus aureus, Kelebsella pneumonia and Escherichia coli via well diffusion method, and showed significant activity compared to the unloaded drug. Furthermore, an antitumor efficacy against HCT-116, HepG-2, PC3 and MCF-7 cancer cells revealed the highest cytotoxic efficacy with no influence on healthy cells. These nanodrugs, retaining both antibacterial and anticancer efficacy, have a talented therapeutic potential because of their selective cytotoxicity, connected with the ability to minimize the risk of bacterial infection in a cancer patient who is frequently immunocompromised.